RESPON MASYARAKAT TERHADAP PILKADA 2015 DI DESA PULAU PADANG KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Urlan Tuci; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The purpose of research to known charateristics voters and response of regional head election 2015 at desa pulau padang kecamatan singingi kabupaten kuantan singingi. This research is located at desa pulau padang. The study using the research methods quantitative descriftive with how to use a list of data the selection remains in desa pulau padang. To know how the charateristics of the people to selection bupati and deputy bupati and how the response of againts the results of regional head election at desa pulau padang kecamatan singingi kabupaten kuatan singingi. For the data collection of respondent and used methode observasi and for processing data used a quantitative deskriftive method to the people or someone in voters bupati and deputy bupati cnaraterististic in the regional head election is also very needed, and how to respons to the society against the regional head election because previously of the former bupati is a family of kondidat numbers 1, as bupati and deputy bupati has been designated now how to response of the results of this research of the election for people who are not choise while voters. The results of the research is that as charateristic voters in the desa pulau padang kecamatan singingi kabupaten kuantan singingi of obtained by 78,61%. It shows that the characteristies of voters against the selection is good and the response of against the reseluts of the regional head election then be seen from the rekaputation response and attaced of 75,61%, that the response of against the results of regional head election 2015 in desa pulau padang is good.Key word: Characteristics, Response, Society, Voters